Cover. Issue 11 (17th November 2019) - Celik, Neslihan; Kelly, Beau; Soltys, Kyle; Squires, James E.; Vockley, Jerry; Shellmer, Diana A.; Strauss, Kevin; McKiernan, Patrick; Ganoza, Armando; Sindhi, Rakesh; Bond, Geoffrey; Mazariegos, George; et al.
Abstract : The cover image is based on the Original Article* Technique and outcome of domino liver transplantation from patients with maple syrup urine disease: Expanding the donor pool for live donor liver transplantation by AjaiKhanna** et al., https://doi.org/10.1111/ctr.13721 .***